THEORETICAL STUDY OF CHROMIUM-CHROMIUM MULTIPLE BOND IN COMPLEXES OF CHROMIUM (II) CARBOXYLATE - Guzmán D., A. (2012)
This paper examines the nature of the multiple bond Chrome-chromium complexes of chromium (II) with carboxylate groups, evaluating the structural details and distances correlation between the metal-metal bond with their electronic properties as the energy of the molecular orbital (HOMO, LUMO), global indices (GAP, chemical potential, hardness and softness). Just as the relative effect of different types of carboxylate ligands, in the Chromium-Chromium link and modify properties. The computational calculations were using the semiempirical method (PM3), optimizing the geometry of the molecules. All this was done in the program Q-Chem, using the graphical interface Spartan. We conclude the existence of groups of molecules based on types of ligands, showing a correlation based on their electronic properties related Cr-Cr distance.